Vaccination of travelers: how far have we come and where are we going? - Chen, Lin H.; Hill, David R; Wilder-Smith, Annelies (Expert review of vaccines, 2011)
Vaccine recommendations are a prominent part of health preparations before international travel. We review progress made in the past decade regarding vaccines used primarily by persons traveling from high-income countries to low- and middle-income countries. The combined hepatitis A-B vaccine, the recently licensed Vero cell-derived Japanese encephalitis vaccine and conjugated quadrivalent meningococcal vaccines are discussed. This article provides updates on yellow fever vaccine-associated visceral and neurologic adverse events, indications for influenza vaccine in travelers, the rapid immunization schedule for tick-borne encephalitis vaccine, schedules for postexposure rabies prophylaxis, and new insights about oral cholera vaccines following the outbreak in Haiti. The future should bring vaccines for serogroup B Neiserria meningitidis, dengue and malaria, as well as an inactivated yellow fever vaccine.